Tooth preparations: science & art. Author: Clovis Pagani, Co-workers: Eduardo Galera da Silva, Daniel Maranha da Rocha. Hanover Park, Illinois: Quintessence; 2017. ISBN: 978-1-78698-001-4. - Rodrigues, José Roberto (Brazilian Dental Science, 2017)
Tooth preparations: science & art Autor Author Clovis Pagani - São Paulo State University (Unesp) - Institute of Science and Technology - Restorative Department – São José dos Campos - SP – Brazil. co-workers Eduardo Galera da Silva - São Paulo State University (Unesp) - Institute of Science and Technology - Social and Pediatric Dentistry Department - São José dos Campos – SP – Brazil. Daniel Maranha da Rocha - University of Sergipe - Department of Dentistry of Lagarto- Lagarto - SE - Brazil. Publisher: Quintessence Pub Co; 1 ed. (31 May 2017) Language: English ISBN: 978-1-78698-001-4.